2003
DOI: 10.1002/jctb.814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of municipal compost/limestone/iron mixtures as filling material for permeable reactive barriers for in‐situ acid mine drainage treatment

Abstract: The aim of the present study was to assess the potential of municipal compost as a carbon source for sulfate-reducing bacteria for acid mine drainage bioremediation for use in permeable reactive barriers at high flow rates (>0.1 m d −1 ). Two different mixtures of municipal compost, limestone and zero-valent iron were assessed in two column experiments. The effluent solution was systematically analysed throughout the experiments. At the end of the experiments precipitates from both columns were withdrawn for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 30 publications
3
45
0
1
Order By: Relevance
“…Another new technique, that is being examined and that could be effective in arid zones, involves the reaction of metal-rich AMD with highly concentrated saline brines, which can neutralize the acid and allow the controlled precipitation of marketable metal salts (McConchie, 2003). Other strategies, which can eventually be applied to some dam or pit lake waters, include evaporation processes (McConchie, 2003), the use of permeable reactive barriers, PRBs (Benner et al, 1999;Gibert et al, 2003) or electrochemical techniques (Shokes and Moller, 1999), the latter allowing the recovery of some metals (particularly copper) as a commercial resource. However, when used alone, this approach cannot produce water with a suitable composition for discharge, and the income from metal recovery would seldom compensate the cost of the treatment (McConchie, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another new technique, that is being examined and that could be effective in arid zones, involves the reaction of metal-rich AMD with highly concentrated saline brines, which can neutralize the acid and allow the controlled precipitation of marketable metal salts (McConchie, 2003). Other strategies, which can eventually be applied to some dam or pit lake waters, include evaporation processes (McConchie, 2003), the use of permeable reactive barriers, PRBs (Benner et al, 1999;Gibert et al, 2003) or electrochemical techniques (Shokes and Moller, 1999), the latter allowing the recovery of some metals (particularly copper) as a commercial resource. However, when used alone, this approach cannot produce water with a suitable composition for discharge, and the income from metal recovery would seldom compensate the cost of the treatment (McConchie, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other biogeochemical processes also contribute to metal removal in these systems including precipitation or co-precipitation as hydroxide complexes, sulphides, carbonates, silicates or sulphates, and sorption to organic matter or other solid residuals such as sediment (Waybrant et al 1998;Gusek 2002;Gibert et al 2003;Zagury et al 2006). Aluminium, a trivalent metal, is predominately removed as aluminium hydroxysulphates in VFWs (Thomas & Romanek 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Median DOC and DTN from monthly sampling. Several studies have shown a sulfate reduction rate decline over time in treatment cells that rely on organic matter oxidation (Drury, 2000;Chang et al, 2000;Gibert et al, 2003;Eger and Wagner, 2003). VFB treatment efficiency decreases with age before organic carbon sources are fully depleted as the supply of short chain organics decreases and supplemental carbon is currently introduced to address this issue (Eger and Wagner, 2003;Kalin et al, 2006).…”
Section: Monthly Sampling Resultsmentioning
confidence: 99%